(untitled) (Journal of Parents and Teachers, 2013)
The article introduces the different ways in which technology has been introduced in classrooms in recent times as playing traditional models and how some students have sought ways parallel organization to fill these school gaps. After that, the article introduces social learning theories and their ZPD of Vygotsky and how these zones of proximal development are changing and growing due to use of technology in general and social networking in particular. The article ends with the conclusion of the need to use these environments in teaching and learning processes.